P2X4 Receptor in Silico and Electrophysiological Approaches Reveal Insights of Ivermectin and Zinc Allosteric Modulation - Latapiat, Verónica; Rodríguez, Felipe E.; Godoy, Francisca; Montenegro, Felipe A.; Barrera, Nelson P.; Huidobro-Toro, Juan P. (Frontiers in Pharmacology, 2017)
Protein allosteric modulation is a pillar of metabolic regulatory mechanisms; this concept has been extended to include ion channel regulation. P2XRs are ligand-gated channels activated by extracellular ATP, sensitive to trace metals and other chemicals. By combining in silico calculations with electrophysiological recordings, we investigated the molecular basis of P2X4R modulation by Zn(II) and ivermectin, an antiparasite drug currently used in veterinary medicine. To this aim, docking studies, molecular dynamics simulations and non-bonded energy calculations for the P2X4R in the apo and holo states or in the presence of ivermectin and/or Zn(II) were accomplished. Based on the crystallized Danio rerio P2X4R, the rat P2X4R, P2X2R and P2X7R structures were modelled, to determine ivermectin binding localization. Calculations revealed that its allosteric site is restricted to transmembrane domains of the P2X4R; the role of Y42 and W46 plus S341 and non-polar residues were revealed as essential, and are not present in the homologous P2X2R or P2X7R transmembrane domains. This finding was confirmed by preferential binding conformations and electrophysiological data, revealing P2X4R modulator specificity. Zn(II) acts in the P2X4R extracellular domain neighboring the SS3 bridge. Molecular dynamics in the different P2X4R states revealed allosterism-induced stability. Pore and lateral fenestration measurements of the P2X4R showed conformational changes in the presence of both modulators compatible with a larger opening of the extracellular vestibule. Electrophysiological studies demonstrated additive effects in the ATP-gated currents by joint applications of ivermectin plus Zn(II). The C132A P2X4R mutant was insensitive to Zn(II); but IVM caused a 4.9±0.7-fold increase in the ATP-evoked currents. Likewise, the simultaneous application of both modulators elicited a 7.1±1.7-fold increase in the ATP-gated current. Moreover, the C126A P2X4R mutant evoked similar ATP-gated currents comparable to those of wild-type P2X4R. Finally, a P2X4/2R chimera did not respond to IVM but Zn(II) elicited a 2.7±0.6-fold increase in the ATP-gated current. The application of IVM plus Zn(II) evoked a 2.7±0.9-fold increase in the ATP-gated currents. In summary, allosteric modulators caused additive ATP-gated currents; consistent with lateral fenestration enlargement. Energy calculations demonstrated a favorable transition of the holo receptor state following both allosteric modulators binding, as expected for allosteric interactions.